암 극복 베하스운동 프로그램이 유방암 환자의 위기와 불안에 미치는 효과 - 김선애(Kim, Sun Ae); 김종임(Kim, Jong Im); 박선영(Park, Sun Young) (근관절건강학회지, 2014)
Purpose: The purpose of this study was to estimate the effects of a cancer-overcome BeHaS exercise program on post-trauma risk and anxiety in breast cancer patients. The cancer-overcome BeHaS exercise program consisted of exercise, education, and cognitive supports. Methods: A one group pretest-posttest experimental design was used for this study. Fourteen mastectomy patients, the subjects of the group participated in the BeHaS exercise program. The program was provided for 8 weeks, once a week in C hospital. Data were collected from October to November 2012 with self report structured questionnaires. Descriptive statistics, and Wilcoxon Signed Rank test were used to analyze data with the SPSS 19.0. Results: The mean age of participants was 53 and the mean postoperative period after the surgery was 18.64 months. After the BeHaS exercise program, while there was no significant decrease in post-trauma risk scores, there was a significant difference in anxiety (z=-2.20, p=.028). Conclusion: This program has effects on decreasing anxiety in patients with breast cancer. Therefore the BeHaS exercise program should be applied as a nursing intervention to reduce anxiety for the patients with breast cancer.